Graphene Diodes: Graphene in 2D/3D Heterostructure Diodes for High Performance Electronics and Optoelectronics (Adv. Electron. Mater. 7/2021). (9th July 2021) - Wang, Zhenxing; Hemmetter, Andreas; Uzlu, Burkay; Saeed, Mohamed; Hamed, Ahmed; Kataria, Satender; Negra, Renato; Neumaier, Daniel; Lemme, Max C.
Abstract : In article 2001210, Max C. Lemme and co‐workers highlight recent advances in 2D/3D heterostructures with graphene. The article demonstrates the advantages of metal‐insulator‐graphene diodes and graphene‐silicon Schottky diodes for radio frequency circuit applications and photodetection, with outstanding figures‐of‐merit comparable to or even outperforming the state‐of‐the‐art technology.